HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP REMAJA PUTRI TENTANG SADARI SEBAGAI DETEKSI DINI KANKER PAYUDARA DI SMA NEGERI 2 MENGWI BADUNG - Ni Ketut Noriani (JURNAL MEDIKA USADA, 2023)
Background: Female adolescent who get their first menstruation earlier have a longer exposure to the estrogen hormone in their lives; so that, the potential for abnormalities in the breast is quite large. Early detection is a very important step to reduce the death rate due to breast cancer which can be done by means of Breast Self-Examination (BSE). Aim: To determine the correlation between the level of knowledge and attitude of female adolescent on BSE as an early detection of breast cancer at SMA Negeri 2 Mengwi. Method: This study employed correlational analysis design with a cross-sectional approach. There were 69 women in childbearing age who were involved as the sample recruited as the sample through simple random sampling technique. Data were collected using a questionnaire and analyzed with the Spearman Rank test. Finding: The finding showed that the majority of the respondents had good knowledge with 34 respondents (49.3%), and 37 repondents (53.6%) had good attitude on BSE. The Spearman Rank test results (Rho) obtained p value = 0.000 <0.05 meant H0 was rejected and Ha was accepted which indicated there was a correlation between the level of knowledge and attitude of female adolescent about BSE as early detection of breast cancer. Conclusion: Based on the study, it can be concluded that the higher level of knowledge, the female students will tend to have a positive attitude toward breast cancer prevention by doing BSE, and this is because female students tend to feel very scared and worried about having breast cancer which can result in death in the sufferer